Anti-arrhythmia and anti-lipid peroxidation effects of methylflavonolamine - Dun Wen; Yang Li-zhi; Zhou Er-feng; Liang Yue-qin (Acta Pharmacologica Sinica, 2016)
Effects of methylflavonolamine (MFA) on arrhythmias induced by myocardial reperfusion were studied with rat hearts in situ and in vitro. In pentobarbital-anesthetized rats, MFA (20 mg.kg-1, i.v.) pretreatment reduced the incidence of reperfusion-induced ventricular fibrillation after left descending coronary artery ligation (15 min) and reperfusion (3 min) (28.6% vs 85.7% in control, P less than 0.05). Malondialdehyde (MDA) production (85 +/- 9 nmol/g wet wt) was inhibited in myocardium from the reperfused area in comparison with control (133 +/- 15 nmol/g wet wt). In isolated rat hearts with local ischemia (15 min) and reperfusion (1 min), MFA 5 mumol.L-1 (perfused 10 min prior to coronary artery ligation) prevented reperfusion-induced arrhythmias (0% vs 85.7% in control, P less than 0.01). In myocardium from the reperfused area, superoxide dismutase (SOD) and catalase (Cat) activity was increased and xanthine oxidase (XOD) activity, MDA production and nonesterified fatty acids (NEFA) contents were decreased. The results show that MFA prevents reperfusion-induced arrhythmia by inhibiting lipid peroxidation and regulating the metabolism of NEFA